educational methods (The meanings of softness and roughness in the Holy Quran) (Journal of the College of Basic Education, 2022)
Praise be to God, praise that fulfills His blessings, rewards His abundance, and defends us from affliction and vengeance. Praise be to God, who made us from the nation of the Qur’an this great treasure whose wonders do not end until the advent of the Hour, as the Chosen One, may God’s prayers and peace be upon him, and his good and pure family, his mujahideen companions and those who followed them with kindness until the Day of Judgment and after told us. .., The Qur’anic topics and investigations were very numerous among students of scientific research, and their titles and the investigations they dealt with varied, and that among the topics and colors of objective interpretation is the objective interpretation of the term, which is specific to this color of terms.